The co-production of an intervention facilitating informal caregivers to support adults at risk of suicide and serious self-harm: A brief report - Frances, Debbie (Journal of Recovery in Mental Health)

(untitled) (Ontario Shores Centre for Mental Health Sciences, 2024)
The recovery model in mental healthcare increasingly recognises suicidal behaviour as an interpersonal issue, with caregivers seen as essential in prevention. In the UK, as in other parts of the world, there is growing consensus in policies, guidelines and academic research towards carer involvement in a person’s mental healthcare, yet inconsistency in practice remain commonplace.In response to the theme of poor family involvement consistently identified in reports into deaths by suicide in Devon (UK), Devon Partnership NHS Trust has developed Stronger Together, a training programme for carers of suicidal adults. The programme, co-produced with carers and service users, also includes a collaborative learning component with healthcare staff.This report explores the programme's co-production and my personal involvement. Co-production shaped Stronger Together, aligning it with national policy and research findings. Its co-delivery and co-learning approach uniquely addresses carers' needs and fosters staff-carer collaboration. Learning from this initiative could help other mental health trusts foster a culture of carer collaboration, potentially improving patient safety, reducing caregiver burden and enhancing support for patients and families to reduce deaths by suicide. It also strengthens the case for co-production of training that effectively meets the needs of participants and delivers on its outcomes.